Governing carbon markets with distributed ledger technology - Marke, Alastair; Mehling, Michael; Corrêa, Fabiano de Andrade, 1982- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2022)
Carbon markets involve complex governance challenges, such as ensuring transparency of emissions, facilitating as well as recording transactions, overseeing market activity and preventing abuse. Conventionally, these have been addressed with a combination of regulatory, procedural and technical structures that impose significant burdens on market participants and administrators while remaining vulnerable to system shocks and illicit practices. Distributed Ledger Technology (DLT) has the potential to address these problems. This volume offers the first book-length exploration of how carbon markets can be governed using DLT, offering conceptual and theoretical analysis, practical case studies, and a roadmap for implementation of a DLT-based architecture in major existing and emerging carbon markets. It surveys existing expertise on distributed ledger technology, provides progress updates from industry professionals, and shows how this technology could offer a cost-effective and sustainable solution to double-counting and other governance concerns identified as major challenges in the implementation of carbon markets.
Understanding 'distributed ledger technology' and its potential as a disruptive technology for climate action -- Governing the carbon market -- Potential interaction between Artificial Intelligence, internet of things and DLT -- Emerging technologies and their applicability to solve challenges in the carbon markets : an overview -- Transition to a DLT-supported governance framework -- DLT and the European Emissions Trading System -- DLT and the voluntary carbon market -- The Carbon Offsetting and Reduction Scheme for International Aviation (CORSIA) -- DLT and networked carbon markets -- Conclusions, recommendations and a potential pathway for a transition to a DLT based governance for carbon markets.
Title from publisher's bibliographic system (viewed on 15 Aug 2022).
Keywords: Emissions trading -- Law and legislation; Carbon offsetting -- Law and legislation; Blockchains (Databases) -- Law and legislation